Certified Interdisciplinary Teachers’ Perception of The Implementation of Teacher Certification Program - Rusnah Rusnah; I Gusti Ngurah Darmawan; Sunardi Sunardi; Istanti Hermagustiana (Teacher Training and Education Faculty, Widya Gama Mahakam Samarinda University, 2023)
Background: The implementation of teacher certification programs (TCPs) has been a topic of interest in education research. Previous studies have primarily focused on student and teacher outcomes, with limited attention given to teachers' perceptions of TCPs. This study aims to address this gap by exploring the perception of certified interdisciplinary teachers regarding the implementation of a TCP in Indonesia. By understanding teachers' perspectives, this research contributes to the evaluation and improvement of TCPs, ultimately enhancing the quality of education.Methodology: This study adopts a qualitative research design, specifically a multiple case study approach. Five certified senior high school teachers from public schools in East Kalimantan, Indonesia, were selected as participants. Data collection methods included semi-structured interviews and document analysis of the teachers' lesson plans. Thematic analysis was conducted using NVivo 12 software.Findings: The findings of the study reveal two primary emerging themes. Firstly, teachers' motivation and expectations regarding the TCP were explored. Secondly, the study examined the perceived benefits of the program. The teachers reported improvements in pedagogical knowledge, curriculum understanding, content knowledge, lesson planning, and teaching performance. The TCP also enhanced their awareness of students' characteristics and needs, fostering stronger teacher-student relationships.Conclusion: The study highlights the importance of purposeful, continuous, and systematic professional development in enhancing teachers' competencies. It emphasizes the need for sustained professional development and regular evaluation of teachers' practices. The findings provide valuable insights for the organizers of TCPs, contributing to program evaluation and improvement.Originality: This study fills a gap in knowledge by exploring the perception of certified interdisciplinary teachers regarding the implementation of a TCP in Indonesia. It contributes to the limited research on teachers' perspectives of TCPs and emphasizes the significance of teacher perception and motivation in professional development programs